Cancer epigenetics in solid organ tumours: A primer for surgical oncologists. Issue 5 (May 2019) - Drake, Thomas M.; Søreide, Kjetil
Abstract: Cancer is initiated through both genetic and epigenetic alterations. The end-effect of such changes to the DNA machinery is a set of uncontrolled mechanisms of cell division, invasion and, eventually, metastasis. Epigenetic changes are now increasingly appreciated as an essential driver to the cancer phenotype. The epigenetic regulation of cancer is complex and not yet fully understood, but application of epigenetics to clinical practice and in cancer research has the potential to improve cancer care. Epigenetics changes do not cause changes in the DNA base-pairs (and, hence, does not alter the genetic code per se) but rather occur through methylation of DNA, by histone modifications, and, through changes to chromatin structure to alter genetic expression. Epigenetic regulators are characterized as writers, readers or erasers by their mechanisms of action. The human epigenome is influenced from cradle to grave, with internal and external life-time exposure influencing the epigenetic marks that may act as modifiers or drivers of carcinogenesis. Preventive and public health strategies may follow from better understanding of the life-time influence of the epigenome. Epigenetics may be used to define risk, to investigate mechanisms of carcinogenesis, to identify biomarkers, and to identify novel therapeutic options. Epigenetic alterations are found across many solid cancers and are increasingly making clinical impact to cancer management. Novel epigenetic drugs may be used for a more tailored and specific response to treatment of cancers. We present a primer on epigenetics for surgical oncologists with examples from colorectal cancer, breast cancer, pancreatic cancer and hepatocellular carcinoma.